Exploring the health consequences of armed conflict: the perspective of Northeast Ethiopia, 2022: a qualitative study - Mulugeta Wodaje Arage; Henok Kumsa; Mulu Shiferaw Asfaw; Abebe Tarekegn Kassaw; Ephrem Mebratu Dagnew; Abayneh Tunta; Woldeteklehymanot Kassahun; Amanuel Addisu; Molla Yigzaw; Tilahun Hailu; Lebeza Alemu Tenaw (BMC, 2023)
Abstract Background Conflict is a complicated topic with a multidimensional consequences for community health. Its effects have a broad pattern, starting from direct war-related morbidity and mortality caused by bullets and bombs to indirect consequences due to the interruption of the delivery of preventive and curative health services. This study aimed to explore the health consequences of the northern Ethiopian conflict in the North Wollo zone, northeast Ethiopia, in 2022. Methods This descriptive qualitative study was conducted from May to June 2022 on six conflict-affected Woredas in the north Wollo zone. A total of 100 purposively selected participants, which included patients, pregnant women, elders, community and religious leaders, and health professionals, were interviewed using IDI and FGD. The data was entered, coded, and analyzed using Open Code version 4.03. Thematic analysis approach employed to conduct the interpretation. Data was presented using descriptive statistics in the form of texts and tables. Results The findings indicate that the conflict has caused a profound consequence on population health. It has resulted in a wide range of direct and indirect consequences, ranging from war-related casualties, famine, and disruptions of supply chains and forced displacement to instances of violence and rape associated with insecurity. The conflict also caused a breakdown in the health system by causing distraction of health infrastructure, fleeing of health workers and shortage of medication, together with insecurity and lack of transportation, which greatly affected the provision and utilization of health services. Additionally, the conflict has resulted in long-term consequences, such as the destruction of health facilities, interruption of immunization services, posttraumatic stress disorders, and lifelong disabilities. The coping strategies utilized were using available traditional medicines and home remedies, obtaining medications from conflict-unaffected areas, and implementing home-to-home healthcare services using available supplies. Conclusion The Northern Ethiopian conflict has an impact on community health both directly and indirectly through conflict-related causalities and the breakdown of the health system and health-supporting structures. Therefore, this study recommends immediate rehabilitation interventions for damaged health infrastructure and affected individuals.